Efeito de antimicrobianos sobre biofilmes de stenotrophomonas maltophilia em diferentes estágios de formação - Carvalhais, Bárbara Ellen Santos (2018)
Stenotrophomas maltophilia is a non-fermenting carbohydrate Gram-negative bacillus, which although of environmental origin, has been reported in bacteremias related to catheter use, urinary tract infections, endocarditis, and respiratory tract infections, especially in immunosuppressed patients. In addition to the intrinsic resistance to several antimicrobials, another characteristic of S. maltophilia that makes it an important opportunistic pathogen is its ability to form biofilms. Thus, our objective was to evaluate the effect of antimicrobials indicated for the treatment of S. maltophilia infections on biofilm in different stages of formation (adhesion, exponential growth and maturation). We evaluated 19 clinical samples and one reference sample (ATCC 13637) of S. maltophilia identified by biochemical methods and confirmed by amplification of the 23S region of ribosomal RNA. Samples were evaluated for similarity by ERIC-PCR. After this initial characterization, the samples were submitted to the following tests: (i) biofilm formation capacity; (ii) biofilm formation kinetics; (iii) antimicrobial susceptibility profile to chloramphenicol (CHL), levofloxacin (LVX), ceftazidime (CAZ), sulfamethoxazole-trimethoprim (SXT) and gentamicin (GEN) by the broth microdilution method and (iv) determination of the minimum inhibitory concentration of antimicrobial agents against biofilm (MIC-b) at different stages of formation. The samples showed genetic heterogeneity in the technique used. All were moderate producers of biofilm, showing adhesion until the 4th hour of incubation, exponential growth between the 4th and 8th hour and mature biofilm between 8 and 24 hours of incubation. All clinical samples in their planktonic forms were sensitive to LVX and SXT and most were sensitive to CHL. Higher resistance frequencies were for CAZ and GEN. We observed that bacterial susceptibility decreases as the biofilm becomes mature. The antimicrobial with the best biofilm activity regardless of the formation time was GEN followed by LVX. SXT which is the first choice antimicrobial for the treatment of S. maltophilia infections was the least effective against biofilms along with CAZ. The determination of the susceptibility profile of the samples in the biofilm shows that GEN was the best antimicrobial activity at all formation times. CAZ was the least effective against 24 hour biofilm and SXT was the least effective in 4 and 6 hour biofilm. Considering the MIC-b/MIC ratio, we can organize antimicrobials in the following decreasing order of activity against mature (24h) biofilms: GEN, LVX, CHL, SXT and CAZ. Based on these findings, we conclude that GEN may be a good option against infections related to S. maltophilia biofilms in regions where this microorganism is susceptible to aminoglycosides. LVX remains a good option against S. maltophilia biofilms. On the other hand, SXT that is currently considered the gold standard for infection by S. maltophilia should not be used in infections where biofilms may be present.